The Urgency of A Husband's Wife's Jealousy Towards Household Harmony (A Perspective of Tuan Guru in East Lombok District) - Muhammad Khotam Zam Zami; Masnun; Zainal Arifin Munir; M. Rifqi Subakti Bahtiar (Cyber Media Indonesia, 2024)
Jealousy is a complex emotion that can cause feelings of suspicion, anger, fear, or humiliation. Jealousy can attack people of all ages and often appears when people feel threatened. This research aims to determine the phenomenon of jealousy between husband and wife in the East Lombok district. Method: This research is qualitative, using field studies with a technical phenomenological approach to data findings from interviews, observations and documentation. Data analysis was done using the reduction method, and the results were displayed in descriptive form. Result: The results of this research show that: 1) The understanding of married couples in the East Lombok district about jealousy is different from the actual concept of jealousy. 2) Tuan Guru should actively teach the community about the concept of building a family, specifically in the chapter on jealousy. Because Tuan Guru, as a religious figure, is at the forefront of shaping public understanding. 3) Tuan Guru, as a religious figure, conveys more good steps in expressing jealousy.